1991
DOI: 10.1039/p29910000951
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduction potential on the rate of reduction of nitroacridines by xanthine oxidase and by dihydro-flavin mononucleotide

Abstract: The cytotoxicity of many nitroaromatic compounds is mediated by bioreduction. There is a correlation between the one-electron-reduction potentials and cytotoxic potencies of simple nitroheterocycles such as nitroimidazoles, but no such correlation is observed with DNA-binding nitroacridines related to the drug nitracrine. A study of the reduction of 1-nitroacridines by the enzyme xanthine oxidase and by reduced flavin mononucleotide, FMNH, (as a model of the enzyme's active site) has been undertaken to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
(1 reference statement)
3
13
0
Order By: Relevance
“…Correlations reported by Orna et al [18] and O'Connor et al [24] between the logarithm of V max and V max / K m and single or two electron reduction potential values for the reduction of aromatics by other flavoenzymes, such as cytochrome P450 reductase, spinach ferredoxin reductase, or xanthine oxidase, might as well be explained in the framework of the complete ping‐pong kinetic schemes discussed here.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Correlations reported by Orna et al [18] and O'Connor et al [24] between the logarithm of V max and V max / K m and single or two electron reduction potential values for the reduction of aromatics by other flavoenzymes, such as cytochrome P450 reductase, spinach ferredoxin reductase, or xanthine oxidase, might as well be explained in the framework of the complete ping‐pong kinetic schemes discussed here.…”
Section: Discussionsupporting
confidence: 54%
“…This can be derived from the fact that the rate equation for this model predicts that k cat = k 2 . Therefore, the observation of a correlation between the natural logarithm of k cat and E(LUMO) of the polynitroaromatic substrates requires the re‐evaluation of the kinetical model often used to describe the oxidation of flavine‐dependent reductases [14,16,18,24,34,35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of the rates of reduction of nitroarenes by free, reduced flavin mononucleotide (FMNH 2 ) [79,112] or by xanthine/xanthine oxidase [80,112] in the absence of oxygen have revealed a similar redox dependence. These studies, and earlier work [113] showed that reduction proceeds to the hydroxyamine (four electrons) via the formation of the nitro radical-anion (one electron reduction) [114], which is probably the rate-limiting step.…”
Section: Redox Properties and The Rates Of Reductive Activationmentioning
confidence: 94%